EXTENDING THE MARKETABILITY OF TOMATO FRUITS AND ENHANCING THEIR QUALITY THROUGH GENE SILENCING AND ORGANIC CALCIUM-PECTIN APPLICATION - Maryam S. Elias; Kadhim D. H. Al-jubouri; Khalil A. Saeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the impact of nine treatments on tomato plants and their planting location within a randomized complete block design. The treatments included gene silencing of the PL enzyme (RNAi-SlPL) and application of organic pectin and calcium to extend the marketability of tomato fruits and improve their quality. The RNAi-SlPL treatment outperformed others, revealed the lowest weight loss (41.4%) and highest firmness (4.89 kg·cm⁻²) after 36 days of cold storage, along with strong performance after 21 days at room storage (41.31% weight loss, 4.29 kg·cm⁻²). This was followed by CaP1P2 treatment, with 43.7% weight loss and 4.48 kg·cm⁻² firmness after 24 days of cold storage, and 45.87% weight loss with 4.15 kg·cm⁻² firmness after 14 days at room storage. Both treatments significantly boosted carotenoid (2.640 and 2.728 mg/100ml respectively) and lycopene (4.62 and 4.81 mg/100ml) levels post- cold storage. These findings highlight the effectiveness of RNAi technology and the use of organic pectin and calcium in extending the marketability of tomato fruits.